Les origines et l’évolution du concept d’acteur - Dussault, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
The actor concept, implicit in former social thought, has become explicit in contemporary studies on international life. It is even more pronounced in the realistic and systemic analysis. The reevaluation of the function of the state underlines the meaning and purpose of relations between nations. Answers vary according to the theoretical rationale.